Evaluation of the elastic properties of an asphalt mix with the addition of recycled polypropylene subjected to a vertical load from the dynamic modulus test. - Portocarrero, Nicole (2023)
n Peru there are a large number of pavements that are in poor condition. One of the main causes is the submission to tensile stress, which generates deformations in the structure. In the last 20 years, Peru has promoted a favorable policy for the construction of road works. This article evaluates the use of polypropylene in the design of the asphalt mix. This is a material that can be recycled and due to the components, it contains, it can be used to improve the properties of asphalt. To design the mixture, the Marshall test was used, since this test evaluates essential parameters to determine if mechanically it behaves adequately to current standards. On the other hand, the Dynamic Modulus test was used to evaluate the expansions of the proposed asphalt mix. To reduce research costs, it was analyzed computationally with the ANSYS Software, since virtual tests of products and systems can be carried out before physical manufacturing. The study was carried out for a highly trafficked urban pavement. The most important factor to evaluate is the resistance to aging produced by the effect of fatigue and the effect of humidity. Therefore, in the present investigation, the preparation of asphalt mixtures modified with recycled polypropylene was analyzed in which the equivalent elastic deformation (DEE), shear stress (EC) and the total deformation of the pavement (DTP) are reduced. Finally, the feasibility and behavior of the proposed mixture was analyzed, making a design with the addition of 5.6% asphalt cement and 2% polypropylene, thus obtaining a decrease in the three main parameters, with 17% in the DEE, 4% in EC and 20% in DT.